Closed-Loop Composite Welding and Bonding System Using Radio-Frequency Heating and Pressure - Enriquez, Ian; Noronha, Colin; Teo, Katrina; Sarmah, Anubhav; Gupta, Surabhit; Nandi, Ankush; Fishbeck, Blake; Green, Micah J.; Vashisth, Aniruddh (MDPI, 2023)
Polymer parts often replace traditional metallic parts in load-bearing applications due to their high strength-to-weight ratio, with thermoplastics at the forefront. Conventional manufacturing processes rely on using fasteners or adhesives to hold composite assemblies together, but thermoplastics can be welded together. Ultrasonic welding is widely used but becomes challenging for complex geometries, and new parameters need to be developed for different polymers and specimen geometries. In this work, we developed a closed-loop welding machine that employs the recent discovery of radio-frequency (RF) heating of carbonaceous materials. The machine is successfully able to weld polylactic acid (PLA) coupons with graphitic RF susceptors at the bondline in less than 2 min and using less than 50 W of input RF power. We found that a higher areal density of the graphitic paint lowers the mechanical properties of the weld because the carbonaceous materials hinder polymer chain diffusion. A significant change was not observed in weld properties for welding pressure ranges between 0 and 0.3 MPa. However, increasing out-of-plane welding displacement increased the modulus and strength of the weld. This work provides an interesting new automated system for welding polymer composites using RF fields, with potential applications in various manufacturing industries.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: closed loop; composites; electromagnetic heating; welding